Building Digital Literacy in the Implementation of Moodle-Based English Learning Management at SMAN 71 - Rita Aryani; Leroy Holman Siahaan (Jurnal Pengabdian Masyarakat Formosa, 2022)
During the Covid-19 pandemic, every individual needs to understand that digital literacy is an important thing needed to be able to participate in the modern world and anticipate the spread of negative information during the Covid-19 pandemic. Digital literacy will create a social order with a critical-creative mindset and outlook. This paper offers the concept of a digital literacy movement that can be implemented during the Covid-19 pandemic. The digital literacy movement that can be carried out during the Covid-19 pandemic is the family digital literacy movement and the community digital literacy movement. The literacy movement aims to improve critical, creative and positive thinking skills in using digital media in everyday life. One of the digital literacy is the use of moodle and the result is 95% effectiveness.